Dimensions of childbirth care associated with maternal satisfaction among low-risk Chilean women. Issue 1 (2nd January 2020) - Pantoja, Loreto; Weeks, Fiona H.; Ortiz, Jovita; Cavada, Gabriel; Foster, Jennifer; Binfa, Lorena
Abstract: The authors of this study aimed to describe the level of maternal satisfaction during labor reported by a national sample of low-risk childbearing women in Chile by identifying the dimensions of intrapartum care most determinant for overall satisfaction. Maternal satisfaction was measured in the postpartum period with an instrument previously validated in Chile. Almost half of the participants (49.4%) reported having optimal satisfaction, 29% adequate, and 22% worse. Treatment of women by professionals and the physical environment were the most important dimension predicting of maternal satisfaction, consistent with findings from developing countries emphasizing patient-provider interaction during labor as a key component of birth care quality.